Modelling and control of a hybrid electric propulsion system for unmanned aerial vehicles - Xie, Ye; Savvaris, Al; Tsourdos, Antonios; Laycock, Jason; Farmer, Andrew (IEEE, 2018)
This paper presents the modelling and control of a hybrid electric propulsion system designed for unmanned aerial vehicles. The work is carried out as part of the AIRSTART project in collaboration with Rotron Power Ltd. Firstly, the entire parallel hybrid powertrain is divided into two powertrains to facilitate the modelling and control. Following this, an engine model is built to predict the dynamics between the throttle request and the resulting output. It is then validated by comparing with experimental data. On the basis of d-q model of the motor/generator, a good estimation of torque loss at steady state is achieved using the efficiency map. Next, a rule-based controller is designed to achieve the best fuel consumption by regulating the engine to operating around its ideal operating line. Following the integration of the models and controller, the component behaviour and control logic are verified via the final simulation. By enabling the engine to operate at its best fuel economy condition, the hybrid propulsion system developed in this research can save at least 7% on fuel consumption when compared with an internal combustion engine powered aircraft.
Keywords: Engines; Torque; Fuels; Biological system modeling; Propulsion; Mechanical power transmission; Batteries